2018
DOI: 10.1016/j.neurobiolaging.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Altered glutamate clearance in ascorbate deficient mice increases seizure susceptibility and contributes to cognitive impairment in APP/PSEN1 mice

Abstract: Ascorbate (vitamin C) is critical as a first line of defense antioxidant within the brain, and specifically within the synapse. Ascorbate is released by astrocytes during glutamate clearance and disruption of this exchange mechanism may be critical in mediating glutamate toxicity within the synapse. This is likely even more critical in neurodegenerative disorders with associated excitotoxicity and seizures, in particular Alzheimer's disease, in which ascorbate levels are often low. Using Gulo mice that are dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 72 publications
(97 reference statements)
2
25
0
Order By: Relevance
“…This H 2 O 2 -associated suppression of glutamate uptake was due to direct oxidation of the sulfhydryl (SH) group of both transporter proteins [169]. In the same regard, a recent study in 2018 identified ascorbate (antioxidant secreted by astrocytes during glutamate clearance) as an essential antioxidant, protective against neuronal excitotoxicity [170]. In this study, ascorbate-deficient mice experienced behavioral changes and increased susceptibility to seizures compared to wild type (WT) mice.…”
Section: Glutamate Uptake In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…This H 2 O 2 -associated suppression of glutamate uptake was due to direct oxidation of the sulfhydryl (SH) group of both transporter proteins [169]. In the same regard, a recent study in 2018 identified ascorbate (antioxidant secreted by astrocytes during glutamate clearance) as an essential antioxidant, protective against neuronal excitotoxicity [170]. In this study, ascorbate-deficient mice experienced behavioral changes and increased susceptibility to seizures compared to wild type (WT) mice.…”
Section: Glutamate Uptake In the Cnsmentioning
confidence: 99%
“…In this study, ascorbate-deficient mice experienced behavioral changes and increased susceptibility to seizures compared to wild type (WT) mice. This led the authors to conclude that low levels of antioxidants could explain the development of subclinical seizures associated with the cognitive impairment in patients with AD, who have a remarkably lower level of ascorbate in their CNS [170].…”
Section: Glutamate Uptake In the Cnsmentioning
confidence: 99%
“…For example, postmortem investigation of patients with AD showed that GLT-1 was expressed more in activated astrocytes, and cognitive functions were preserved better before the patient’s death ( Kobayashi et al, 2018 ). Restoring GLT-1 expression by transgenic or pharmacological approaches in experimental animals significantly improved synaptic damage, Aβ deposition, and cognitive impairments ( Takahashi et al, 2015 ; Mi et al, 2018 ). This suggests that upregulation of GLT-1 expression and uptake for glutamate may be profitable for preserving cognition in AD patients or animal models.…”
Section: Discussionmentioning
confidence: 99%
“…A concentration-dependent relationship between glutamate and ASC in striatum and hippocampal regions (cornu ammonis 1,3 (CA1,3) and dentate gyrus (DG)) has been shown in vivo in rats, highlighting a dynamic interplay between glutamate signaling and ASC fluctuation in the brain, with putative effects on behavioral responses [ 186 , 187 , 188 ]. Upon release, glutamate can be taken up by astrocytes, converted to glutamine and released for neuronal uptake [ 63 , 189 , 190 ]. The uptake of glutamate in astrocytes prompts ASC efflux possibly through induced cellular swelling and volume-sensitive anion channels, releasing ASC, e.g., to diminish glutamate-induced oxidative damage [ 60 , 63 ].…”
Section: Vitamin C Functions In the Brainmentioning
confidence: 99%